A Model for Teaching and Learning Programming Subjects in Public Secondary Schools of Malaysia - Mohamed Salleh F.H.; Dewi D.A.; Liyana N.A.; Md Nasir N.R. (Springer Science and Business Media Deutschland GmbH, 2023)
Education computing; Learning systems; Random access storage; Teaching; Education curriculums; Expert evaluation; Higher School; Learning programming; Malaysia; Modeling component; Programming; Secondary schools; Teaching and learning; Teaching programming; Curricula